Analysis of Lightning Protection and Grounding Effect of Shared Iron Tower. Issue 1 (August 2020) - Xiaopo, Mao; Yaodong, Zhang; Xueming, Zhou; Zhiqiang, Feng; Zeqi, Huang; Xiang, Ren; Tianru, Shi; Jianjin, Fu; Junjie, Huang
Abstract: By analyzing the lightning protection and grounding requirements of the respective systems of the communication base station and the power tower, the impact of the towers on their respective systems is analyzed. By establishing a simulation calculation model of the shared tower's grounding grid, a mature algorithm is used to analyze the current distribution of the typical shared tower. And ground potential distribution, so as to obtain the degree of influence of the equipment when the respective system is struck by lightning. According to the impact, the lightning protection grounding technical requirements and common scheme of the shared iron tower are proposed.